2022
DOI: 10.3390/ijms23073859
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of Caffeic or Chlorogenic Acid on the C32 Cells That Have Simultaneously Been Exposed to a Static Magnetic Field

Abstract: The induction of apoptosis is one of the main goals of the designed anti-cancer therapies. In recent years, increased attention has been paid to the physical factors such as magnetic fields and to the natural bioactive compounds and the possibilities using them in medicine. Hence, the aim of this study was to evaluate the anti-tumor effect of caffeic or chlorogenic acid in combination with a moderate-strength static magnetic field on C32 melanoma cells by assessing the effect of both factors on the apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Plant compounds are widely used in the treatment of various diseases, including cancer. In our previous research, we have already proved the positive effect of chlorogenic and caffeic acid and a static magnetic field on melanoma cells in the aspect of oxidative stress, cell redox homeostasis and apoptosis [ 28 , 33 ]. In turn, Li et al [ 37 ] demonstrated the effectiveness of treatment consisting of a combination of sialic acid modified chlorogenic acid liposome therapy (CA-SAL) in combination with anti-PD1 (anti-programmed death protein 1) antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plant compounds are widely used in the treatment of various diseases, including cancer. In our previous research, we have already proved the positive effect of chlorogenic and caffeic acid and a static magnetic field on melanoma cells in the aspect of oxidative stress, cell redox homeostasis and apoptosis [ 28 , 33 ]. In turn, Li et al [ 37 ] demonstrated the effectiveness of treatment consisting of a combination of sialic acid modified chlorogenic acid liposome therapy (CA-SAL) in combination with anti-PD1 (anti-programmed death protein 1) antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a both polyphenols and a SMF can act synergistically together. Furthermore, we previously demonstrated their synergistic effect in inducing apoptosis in C32 cells [ 28 ] and also that a static magnetic field may be use in the design of new therapeutic strategies for diseases in the pathogenesis of which are played by disturbance of the signaling cascades that are associated with the activity of TGFβ [ 50 ]. Their common effect on cells is rather not due to the influence of a SMF on the structure of molecules [ 51 ], but it results from their similar mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorogenic acid is an esterification product of caffeic acid and quinic acid. They often coexist in Taraxaci Herba , 1 Lonicerae Japonicae Flos , 2 Eucommiae Folium 3 and other traditional Chinese medicines (TCMs) and play many pharmacological roles, such as antioxidation, 4 antiviral, 5 antitumor 6 and anti-inflammatory agents. 7 However, the content of chlorogenic acid and caffeic acid in TCMs is often low, while other coexisting chemical substances are huge, complex and diverse, and their content spans multiple orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%